2014
DOI: 10.4238/2014.december.4.21
|View full text |Cite
|
Sign up to set email alerts
|

MTA1 promotes cell proliferation via DNA damage repair in epithelial ovarian cancer

Abstract: ABSTRACT. We examined whether metastasis-associated gene 1 (MTA1) promotes cell proliferation via DNA damage repair in ovarian cancer. MTA1 was successfully down-regulated using small interfering RNA in the epithelial ovarian cancer cell lines SKOV-3 and OVCAR-3. Cell growth was evaluated through MTT and colony formation assays. Fluorescence-activated cell sorting analysis was used to evaluate the distribution of cells in the cell cycle, and cytotoxicity assays were performed to study cell sensitivity to cispl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 23 publications
(27 reference statements)
0
7
0
Order By: Relevance
“… 13 , 14 Recent studies have identified that MTA1 inhibited differentiation and promoted proliferation in cancer cell lines. 3 , 15 , 16 Though these studies have shown that MTA1 is involved in cancers, the precise role of it in cancers including gastric cancer is not well understood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 13 , 14 Recent studies have identified that MTA1 inhibited differentiation and promoted proliferation in cancer cell lines. 3 , 15 , 16 Though these studies have shown that MTA1 is involved in cancers, the precise role of it in cancers including gastric cancer is not well understood.…”
Section: Discussionmentioning
confidence: 99%
“… 22 Furthermore, MTA1 promotes cell proliferation by enhancing DNA repair in epithelial ovarian cancer cells. 15 …”
Section: Discussionmentioning
confidence: 99%
“…Redox-sensitive proteins also show the influence on cell cycle progression [[78], [79], [80]]. Some authors reported that the cell proliferation can be promoted by enhancing DNA repair [81,82]. Therefore, some of the modulatory effects on DNA damage and repair under the influence if vitamin D 3 and its derivatives might occur as a function of proliferative status rather than induction of stress response pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Redox-sensitive proteins also show the influence on cell cycle progression [78][79][80]. Some authors reported that the cell proliferation can be promoted by enhancing DNA repair [81,82]. Therefore, some of the modulatory effects on DNA damage and repair under the influence if vitamin D 3 and its derivatives might occur as a function of Fig.…”
Section: Discussionmentioning
confidence: 99%